Molecular surveillance of resistance to pyrethroids insecticides in Colombian Aedes aegypti populations. - Yurany Granada; Ana María Mejía-Jaramillo; Sara Zuluaga; Omar Triana-Chávez (Public Library of Science (PLoS), 2021)
Introduction In Colombia, organochloride, organophosphate, carbamate, and pyrethroid insecticides are broadly used to control Aedes aegypti populations. However, Colombian mosquito populations have shown variability in their susceptibility profiles to these insecticides, with some expressing high resistance levels. Materials and methods In this study, we analyzed the susceptibility status of ten Colombian field populations of Ae. aegypti to two pyrethroids; permethrin (type-I pyrethroid) and lambda-cyhalothrin (type-II pyrethroid). In addition, we evaluated if mosquitoes pressured with increasing lambda-cyhalothrin concentrations during some filial generations exhibited altered allelic frequency of these kdr mutations and the activity levels of some metabolic enzymes. Results Mosquitoes from all field populations showed resistance to lambda-cyhalothrin and permethrin. We found that resistance profiles could only be partially explained by kdr mutations and altered enzymatic activities such as esterases and mixed-function oxidases, indicating that other yet unknown mechanisms could be involved. The molecular and biochemical analyses of the most pyrethroid-resistant mosquito population (Acacías) indicated that kdr mutations and altered metabolic enzyme activity are involved in the resistance phenotype expression. Conclusions In this context, we propose genetic surveillance of the mosquito populations to monitor the emergence of resistance as an excellent initiative to improve mosquito-borne disease control measures.